Thermodynamic resolution of periosteal reaction and taphonomic change - B.M. Rothschild; C. Rothschild (PAGEPress Publications, 2003)
There appears to be a need for an objective technique to validate macroscopic visual examination of bone for periosteal reaction. Distinguishing taphonomic (post-mortem environmentally induced) and ontogenic (e.g., growth of subadult bone) changes appears especially problematic. Wide discrepancies in a single sample set (3-7), with respect to periosteal reaction frequency, suggest a need for development of a standardized technique which would be comparable among investigators.